Fatwa dan Produk Hukum dalam Perspektif Ushul Fiqh: Analisis Majelis Taujih Wal Irsyad (MTI) di Lembaga Dakwah Islam Indonesia (LDII) - Mawahib, M. Mahdil; Muttaqin, Amrul (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This article delves into the pivotal role of Fatwas and Legal Products issued by Majelis Taujih Wal Irsyad (MTI) within the Lembaga Dakwah Islam Indonesia (LDII) through the lens of Ushul Fiqh. It explores how LDII, as a prominent religious organization in Indonesia, utilizes the Fatwas and Legal Products provided by MTI as fundamental pillars in regulating the religious practices of Muslims. The study's findings underscore LDII's steadfast adherence to the Qur'an and Hadith in formulating its legal framework, while also incorporating various madhhabs recognized by Ahlus Sunnah wal Jamaah, provided they align with the teachings of the Qur'an and Hadith. Unlike some organizations, LDII does not formulate its own fatwas; rather, it derives its legal rulings directly from the Qur'an and Sunnah. The educational approach within LDII emphasizes the significance of students and teachers alike possessing the books being studied, employing the term